Clinical manifestations and evaluation of postmenopausal vulvovaginal atrophy. (3rd August 2021) - Pérez-López, Faustino R.; Vieira-Baptista, Pedro; Phillips, Nancy; Cohen-Sacher, Bina; Fialho, Susana C. A. V.; Stockdale, Colleen K.
Abstract: Introduction: It is estimated that 50% of women will suffer a severe form of vulvovaginal atrophy (VVA) related to menopause. Equally, young women may temporarily present this clinical problem while receiving various pharmacological or endocrine treatments or radiotherapy. Aim: To determine clinical and diagnostic exams required to confirm the presence of VVA (also referred to as atrophic vaginitis, urogenital atrophy, or genitourinary syndrome of menopause) and rule out other genital or pelvic clinical conditions. Materials and methods: Literature review searches were carried out on the main scientific article search engines (PubMed, SciELO, Cochrane) using different clinical terms, treatments or interventions and comorbidity related to VVA. Results: The development and severity of VVA depend mainly on the duration of hypoestrogenism. Hypoestrogenism causes changes in the urogenital tissue, generating signs and symptoms, such as dryness, burning, soreness, itching, and irritation of the genital skin. The diagnosis can be made through anamnesis (patient history), questionnaires, physical exam, and, sometimes, complementary exams. Objective vaginal assessment is essential and can be completed with the Vaginal Health Index, the Vaginal Maturation Index, or vaginal pH in the absence of infection or semen. The exclusion of other vulvovaginal organic pathology is essential to reach an accurate diagnosis and provide adequate treatment. Conclusions: The specialist should be able to identify VVA, rule out other pathologies that make a differential diagnosis and conduct proper management.